Show Us Your Skills: Exploring the Science Communication Landscape in Graduate Education - Ashley McLeod-Morin; Hikaru H Peterson; Lauri Baker; Garrett Steede; Sadie Hundemer; Rebecca Swenson; Troy McKay (Journal of Applied Communications, 2025)
Funding, public debate, behavior change, and policy support often depend upon effectively communicating scientific relevance and research outcomes effectively, but many graduate programs do not build the skills needed for graduates to confidently engage public audiences and share their work through science communication. The purpose of this exploratory study was to understand graduate students’ perceptions of the need for science communication skills compared with science communication experts, graduate students’ perceived science communication abilities, and the opportunities they have to gain these skills at their institutions of higher education. A survey of graduate students at two land-grant universities was conducted (n = 158) to address this purpose. The results of this study support the importance of science communication skills and experiences for graduate students in agricultural and natural resources fields. Overall, the graduate students that participated in this study ranked the perceived importance of science communication skills similarly to the expert ranking reported in previous work. Graduate students placed less importance on skills they reported being less effective in and reported an interest in obtaining more experience and skills in all areas of science communication. Implications from this work are opportunities for faculty in agricultural and natural resources communication to create science communication skill development experiences for graduate students. Opportunities exist for fellowships and partnerships with industry and science communication centers to help graduate students gain experiences and skill development in science communication.
Keywords: science communication; graduate students; survey; science communication training